(untitled) (Bangladesh Journal of Animal Science, 2022)
Reproductive anatomy is vital for successful reproductive management and has significance for application of assisted reproductive biotechnology. This study was carried out to characterize biometrically and histologically reproductive organs of 50 slaughtered female cattle (<3 years; n=25, 3 to ≤5 years; n=25). The measurements (length, weight and width) of the right segment of the studied reproductive organs were greater compared to the left segment. No significant difference (p>0.05) was observed between left and right ovary length, width and weight within and between age groups. The length of ovaries were 1.92±0.19 cm and 1.95±0.04 cm at <3 years; 2.16±0.21 cm and 2.17±0.19 cm at 3 to ≤5 years; width were 1.09±0.14 cm and 1.17±0.10 cm at <3 years and 1.31±0.10 cm and 1.46±0.11 cm at 3 to ≤5 years and the weight were 1.77±0.41 gm and 2.20±0.57 gm at <3 years; 1.79±0.45 gm and 2.54±0.14 gm at 3 to ≤5 years in the left and right ovaries, respectively. Oviduct length, width and weight did not differ significantly (p>0.05) between the left and right oviducts within and between the age groups. Oviduct length (16.36±0.78 and 17.58±0.97 cm), width (0.21±0.02 and 0.26±0.33 cm) and weight (0.72±0.03 and 0.81±0.11 gm) was found for the right oviduct at <3 years and 3 to ≤5 years and for left oviduct length, width and weight were 16.20±0.65 and 16.64±0.86 cm; 0.19±0.02 and 0.23±0.03 cm; and 0.69±0.04 and 0.79±0.13 gm, at <3 years and 3 to ≤5 years, respectively. However, uterine horn length differed significantly (p<0.05) between age groups in the left (16.18±1.18 vs 27.45±2.98 cm) and the right horn of the uterus (17.45±1.40 cm vs 28.35±2.88 cm). On the other hand, uterine horn width and weight were not differed significantly between the left and right segments within and between the age groups. Uterus body length and weight were significantly (p<0.05) higher at 3 to ≤5 years compared to <3 years old cow. The average weight, length and width of uterine body were 44.40±7.33 gm vs 21.49±5.91 gm; 7.89±0.61 cm vs 5.87±0.43 cm; 3.46±0.27 cm vs 2.76±0.34 cm at <3 years and 3 to ≤5 years, respectively The whole uterus weight was also differed significantly (p<0.05) at <3 years (47.18±14.92 gm) and 3 to ≤5 years (86.07±11.98 gm). Histological studies showed ideal characteristics of cattle oviduct and uterus. In nutshell, the right ovary was larger in length, wider in diameter, and heavier in weight as compared to left one in indigenous cattle of Bangladesh. Bangladesh Journal of Animal Science 51 (4): 169-177